ASSESSING THE EFFECT OF AIRLINE SERVICE QUALITY ON IMAGE AND POST PURCHASE BEHAVIORAL INTENTION - Ramjit Singh; Abid Suhail Nika (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2020)
The present study aimed to investigate the effect of airline service quality on image and post-purchase behavioral intention among the passengers. The exploratory cum descriptive research design was adopted. The purposive sampling technique was chosen to select valid respondents. Four hundred questionnaires were considered valid, and SPSS 25.0 was used to feed and analyze the data. The data for the study was collected through primary as well as secondary sources. The present study's essential findings are that better service quality affects airline image and post purchase behavioral intention of passengers positively. Moreover, a favorable airline image too affects the behavioral intention of passengers positively. The present research revealed that it is a better service quality and sharp airline image in a highly competitive environment that helps the airlines survive and increase their share in the market. The essential suggestions in terms of service quality dimensions have been put forth by the researcher to airline managers, which can surely improve passengers' memorable experiences.